Pictorial review of rectal carcinoma: a single centre MRI experience in SASMEC @IIUM - Haroon, Raihanah; Wan Chek, Wan Ahmad Firdaus (2022)
PICTORIAL REVIEW OF RECTAL CARCINOMA: A SINGLE CENTRE MRI EXPERIENCE IN SASMEC @IIUM Wan Ahmad Firdaus Wan Chek1, Raihanah Haroon2 1Radiology Department, Kulliyyah of Medicine, IIUM firdauswan91@gmail.com 2Radiology Department, Kulliyyah of Medicine, IIUM raihanahharoon@iium.edu.my